An Analysis of The Most Frequent Grammar Errors In University Students’ Instagram Comments - Suryo Dewantoro Joyodiningrat; Mira Ermita; Wahyudin Ahmadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the most common grammatical errors in Instagram comments written by students of Panca Sakti University Bekasi from the English Education Study Program. Using a descriptive qualitative method, twenty comments were collected, of which sixteen contained grammatical errors while the remaining four comments were error-free regarding the six types analyzed. The analysis focused on subject-verb agreement, sentence fragments, spelling, parallelism, prepositions, and passive voice. The results indicate that subject-verb agreement errors were the most dominant, accounting for 51% of the total errors, followed by sentence fragments (20%), spelling errors (13%), and parallelism and preposition errors (8% each). Passive voice errors were not found in the data. The findings suggest that students’ English usage in informal digital communication tends to be simple, concise, and meaning-focused, often influenced by first language transfer and the fast-paced nature of social media. These patterns contribute to the prevalence of grammatical errors, particularly in subject-verb agreement and sentence completeness.